Institutional factors affecting Foreign Direct Investment in Ukraine : dissecting the Worldwide Governance Indicators (2013-2023) - Shevchenko, Vladyslava; Abdallah, Kareem Issam; Mammadov, Orkhan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis investigates how institutional quality shapes foreign direct investment (FDI) inflows to Ukraine, with a particular focus on the dynamics of the Worldwide Governance Indicators (WGI) between 2002 and 2023. The study aims to determine whether WGI indicators influence FDI, identify which institutional dimension has the strongest effect, and examine the specific role that corruption plays in shaping investment behaviour. Using annual time-series data, regression models with Newey–West standard errors, and both level and first-difference specifications, the analysis evaluates institutional performance alongside macroeconomic controls and major crisis events. The results show that level values of institutional indicators do not significantly explain variations in FDI, as inflows are largely dominated by external shocks such as the 2014 conflict, the COVID-19 pandemic, and the 2022 full-scale invasion. However, the dynamic models reveal that improvements in the control of corruption are strongly and consistently associated with higher FDI inflows, even when accounting for crisis years and short-term investment reversals. Political stability and voice and accountability also demonstrate positive, though less robust, effects. The thesis highlights that meaningful institutional reforms and anti-corruption improvements, which play a crucial role in enhancing Ukraine’s investment climate, while gradual institutional changes have limited short-term impact.
Vedoucí práce: Kareem Issam Abdallah
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses